2002
DOI: 10.1021/tx010151v
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytochrome P450 1a1 and 1b1 in the Metabolic Activation of 7,12-Dimethylbenz[a]anthracene and the Effects of Naturally Occurring Furanocoumarins on Skin Tumor Initiation

Abstract: The current study was designed to determine the mechanistic basis for differences in the effects of naturally occurring furanocoumarins on skin tumor initiation by 7,12-dimethylbenz[a]anthracene (DMBA). Female SENCAR mice were pretreated topically with bergamottin, imperatorin, or isopimpinellin (100-3200 nmol), 7,8-benzoflavone (7,8-BF, 5-40 nmol, a known inhibitor of DMBA skin carcinogenesis in mice), or acetone (vehicle control) 5 min prior to topical treatment with DMBA (10 nmol). Imperatorin, isopimpinell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 33 publications
8
64
0
Order By: Relevance
“…They are involved in the metabolic activation of the polycyclic aromatic hydrocarbons, which are procarcinogens commonly found in our environment (40). We have studied the effect of these phytochemicals on CYP1B1 because the inhibition of CYP enzymes seems to be beneficial in the prevention of DMBA-DNA adduct formation in vivo and in vitro (41).…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in the metabolic activation of the polycyclic aromatic hydrocarbons, which are procarcinogens commonly found in our environment (40). We have studied the effect of these phytochemicals on CYP1B1 because the inhibition of CYP enzymes seems to be beneficial in the prevention of DMBA-DNA adduct formation in vivo and in vitro (41).…”
Section: Discussionmentioning
confidence: 99%
“…Alkylated benz[a]-anthracenes are formed in sediments by thermal processes and have also been identified in cigarette smoke condensate, coal gasification and stock gas particulates, and roofing tar extracts (1, 10). Studies from several laboratories have indicated that DMBA is bioactivated by various isoforms of mammalian cytochrome P-450 and epoxide hydrolase to form DMBA-3,4-dihydrodiol-syn-and anti-1,2-epoxides that react with DNA to form adducts that lead to tumor initiation (22,32,33). An alternative mechanism for metabolic activation is hydroxylation of the alkyl side chain to form hydroxymethyl derivatives, followed by sulfotransferase-catalyzed activation of DMBA to form electrophilic sulfuric acid esters that bind to DNA (6).…”
mentioning
confidence: 99%
“…An alternative mechanism for metabolic activation is hydroxylation of the alkyl side chain to form hydroxymethyl derivatives, followed by sulfotransferase-catalyzed activation of DMBA to form electrophilic sulfuric acid esters that bind to DNA (6). 7,12-Dimethylbenz[a]anthracene has been used as a model polycyclic aromatic hydrocarbon (PAH) in the following ways: (i) as a tumor initiator or as a complete carcinogen in rodent skin and mammary gland models of carcinogenesis (15,22), (ii) as a prototype methyl-substituted PAH in mutation and cancer research (15), (iii) to determine whether metabolic activation occurs via bay-region dihydrodiol epoxide metabolites or hydroxylation of the methyl substituent with subsequent formation of electrophilic sulfuric acid esters (6), and (iv) to determine the environmental fate of methyl-substituted PAHs.…”
mentioning
confidence: 99%
“…Some of these inhibitors of CYP1A1 and 1B1 suppress the tumorigenesis that is induced by a variety of chemical carcinogens (Gelboin et al, 1970;Kinoshita & Gelboin, 1972;Slaga et al, 1977a;El-Bayoumy et al, 1992;Jang et al, 1997;Kleiner et al, 2002Kleiner et al, , 2003El-Bayoumy & Sinha, 2004). In a rat mammary tumour model using DMBA, para-1,4-phenylene-bis(methylene)selenocyanate [also called xyleneselenocyanate] has been shown to have chemopreventive activity (El-Bayoumy et al, 1992;Ip et al, 1994;Prokopczyk et al, 2000) and to inhibit the formation of DMBA-DNA adducts in the rat mammary gland (El-Bayoumy et al 1992).…”
Section: (Viii) Induction Of Cyp1a1 1a2 and 1b1 By Pahsmentioning
confidence: 99%